IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE TO THE VALUE OF COOPERATIVE COMPANY - Rima Elya Dasuki; Ardiyani Lestari (Universitas Pasundan, 2019)
Cooperatives are one of the institution that can carry out economic empowerment for thecommunity. Cooperative business is directly related to the improve the business and welfare ofmembers, so that with good supervision will have a high beneficial impact for members. Cooperativedevelopment policy should give priority to quality of cooperatives, to produces quality cooperativesrequired good supervision. The subject of the result are saving loan cooperatives in West Java-Indonesia . The type of research used in this study is descriptive research methods, namely researchthat uses primary and secondary data which is then processed and analyzed .Implementation of GoodCorporate Governance encourages cooperative management in conducting savings and loanactivities effectively and efficiently by taking into account the principles of cooperatives andprudential principles so that the cooperative assessment is transparent, accountable and responsive.Principles of Good Corporate Governance required by cooperatives to achieve businesssustainability. Research Finding: Management of cooperatives can be done effectively and with theimplementation of Good Corporate Governance the performance of cooperatives can be increasedand improve service to the member. Cooperative development policy should give priority to qualityof cooperatives, to produce quality cooperatives required good supervision.